REGULATION OF THE CORPORATE SOCIAL RESPONSIBILITY CONCEPT IN THE COMPANY LIMITED IN INDONESIA LEGAL PRODUCTS - I Nyoman Yatna Dwipayana Genta (Warmadewa Press, 2019)
Corporate Social Responsibility (hereinafter written CSR) must be legally enforced by a Limited Liability Company that runs business activities in the field and/or related to natural resources in Indonesia. This provision comes into force since the promulgation of Law No. 40 of 2007 concerning Limited Liability Companies, State Gazette of the Republic of Indonesia of 2007 No. 106, Additional State Gazette of the Republic of Indonesia No. 4756 (hereinafter the Limited Liability Company Law). Taking into the problem, this study aims to explore more deeply about the urgency of regulating the concept of CSR from what was initially voluntary and then becoming a legal or mandatory obligation after the enactment of the Limited Liability Company Law. The type of research used in this study is a type of normative legal research, using the type of legislation approach, approach to Legal Concept Analysis and Historical approaches. Based on the result of the study, it can be concluded that the sustainability of the company will be guaranteed if the corporation participates in the interests of stakeholders and the environment in which the Limited Liability Company conducts its activities becomes one of the urgency of regulating the concept of CSR in Indonesian legal products. The basic factors that make the implementation of CSR activities in Indonesia have not run optimally are that there are still weaknesses in the regulation on the regulation of CSR concepts in Indonesia which include restrictions on companies.